Análise da viabilidade da utilização de sistema alagado construído em escoamento vertical (SAC-EV) como ferramenta de tratamento de esgoto descentralizado - Ramos, Sergio Gabriel Ribeiro (Brasil, 2023)
In Brazil, more than half of the sewage generated by the population is treated, however, this is a reality only because the basic sanitation service, which includes the provision of sanitary sewage services, is concentrated in the most populous regions of the country and in its capitals , inland cities located mainly in the North and Midwest of the country do not have access to this type of service. The objective of this work was the implementation of a pioneering project of a Constructed Flooded System with Vertical Flow (SAC-EV) as an alternative tool for decentralized sewage treatment, the project was carried out at the Institute of Education, Agriculture and Environment - IEAA/UFAM , located in the municipality of Humaitá, state of Amazonas. Four collections were carried out to analyze the parameters of pH, Total Solids, Turbidity, Biochemical Oxygen Demand, Dissolved Oxygen, Total Phosphorus, Total Nitrogen, Thermotolerant Coliforms. Among the eight parameters analyzed and compared directly with the standards established by CONAMA resolutions 357 and 430, the SAC-EV was able to meet five of them, highlighting the BOD results where it was removing about 49.36% of organic matter and Nitrogen Total where about 69.15% of the pollutant was degraded within the system, proving to be a likely path to be followed, however further studies are needed to adapt the system to all the particularities of the region.